Power production with Organic Rankine Cycle technology utilizing waste heat from a cracker and three polyethylene units - Hackl, Roman; Perret, Stephanie (My University, 2009)
Growing awareness of the greenhouse effect combined with limited fossil fuel resources are the incentives for implementing energy savings measures and achieving CO2 emission reductions in industry. The process industry has a large potential for energy savings. There is currently increasing interest for energy recovery from excess process heat. Most of the excess heat at Borealis sites in Stenungsund is available at low temperature. This master’s thesis investigated the potential for electric power production using Organic Rankine Cycle technology from low temperature excess process heat from Borealis’ cracker, low pressure PE plants and a new high pressure PE plant. Available excess heat sources were determined by a pinch analysis of the PE units. A pinch analysis of the cracker plant was already available. Possibilities for internal heat exchange are shown for the PE units. 1.5 MW of steam can be saved through internal heat exchangers in the LPPE units. Interesting streams for ORC power production were identified. Case studies were carried out for the most promising excess heat streams, i.e. the loop reactor jacket cooling water and excess LP steam from the new HPPE unit. The jacket water studies showed a potential for electricity production of ca. 1 MWel. Further economic evaluation indicated that the electricity price has to reach ca. 800 SEK/MWh in order for the ORC system to be profitable. In the case of LP excess steam, 10 MWheat of excess steam were identified from which it could be possible to generate ca 1.6 MWel. More detailed investigations of the promising cases identified should be performed both internally and in cooperation with ORC manufacturers to assess the actual feasibility of the project. Changes in national and European regulations, for example subsidies for power generation from waste heat from non renewable sources, will strongly affect the economics of ORC systems.
Keywords: Industriell teknik och ekonomi; Kemiteknik; Miljöteknik; Industrial engineering and economy; Chemical Engineering; Environmental engineering